Komparasi Layanan Video Live Streaming Menggunakan Metode Quality of Service - Hardiyanti, Fitri; Bintoro, Panji; Ratnasari, Ratnasari; Herdian Andika, Tahta; Ardhy, Ferly; Eko Setiawan, Agustinus (Jurnal Algoritma, 2024)
Video streaming is growing very rapidly nowadays, many people use it in their daily lives, especially since the pandemic, video streaming has become an important need. Video conferencing applications such as Zoom, Google Meet, and Cisco Webex have become increasingly important in facilitating remote communications, allowing people to communicate, collaborate, and hold virtual meetings without geographic restrictions. This research uses the QoS method to analyze the comparison of service quality from video streaming such as Zoom, Cisco Webex and Google Meet. From the results of the research carried out, each video stream was assessed with QoS. The research carried out was by testing 3 applications, namely Zoom, Cisco Webex and Google Meet, the best results were obtained, namely Zoom with a Throughput value of 6685842, a Delay value of 47ms, a Jitter value of 47 ms and a Packet Loss value of 0.004%. The QoS method can be applied in comparative quality analysis in testing video streaming service applications.